'La dolce vita' meets 'the nature of evil': the paratextual positioning of Italian crime fiction in English translation. (3rd May 2016) - Maher, Brigid
ABSTRACT: In this article I explore the way Italian crime fiction is presented to prospective Anglophone readers through paratextual bindings: titles, cover images and blurbs. I focus in particular on the way Italian settings are – variously – described, elucidated, emphasised and promoted, as publishers and their marketing teams seek to place a text within a space of familiarity or exoticism. Through the very act of circulation across cultures and languages, new forms of national allegory are attributed to these crime novels, on the basis of the perceived needs and prior associations of their new readership.